2015
DOI: 10.3390/cosmetics2030277
|View full text |Cite
|
Sign up to set email alerts
|

Portable EDXRF for Quality Assurance of Cosmetics

Abstract: Portable Energy Dispersive X-ray Fluorescence is a viable, cost and time effective analytical technique for qualitative and quantitative evaluation of a wide range of samples. The objective of this study is to present a methodology for quantification of nail polishes, eye shadows, lipsticks and lip gloss using thin film geometry. The samples were applied over thin films, simulating its use on face and nails. It was possible to quantify S, K, Ca, Ti, Mn, Fe, Cu, Zn, Br, Rb, Sr, Ba and Bi. The methodology is via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Melquiades et al presented a methodology for quantification of S, K, Ca, Ti, Mn, Fe, Cu, Zn, Br, Rb, Sr, Ba, and Bi in nine eyeshadows samples and others cosmetics products using thin film geometry for the portable EDXRF apparatus. The elements range of concentrations found by the authors were compared with our findings (Table ), and Ti, Mn, and Fe were found in all samples in our research and work of Melquiades et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melquiades et al presented a methodology for quantification of S, K, Ca, Ti, Mn, Fe, Cu, Zn, Br, Rb, Sr, Ba, and Bi in nine eyeshadows samples and others cosmetics products using thin film geometry for the portable EDXRF apparatus. The elements range of concentrations found by the authors were compared with our findings (Table ), and Ti, Mn, and Fe were found in all samples in our research and work of Melquiades et al .…”
Section: Resultsmentioning
confidence: 99%
“…Melquiades et al presented a methodology for quantification of S, K, Ca, Ti, Mn, Fe, Cu, Zn, Br, Rb, Sr, Ba, and Bi in nine eyeshadows samples and others cosmetics products using thin film geometry for the portable EDXRF apparatus. The elements range of concentrations found by the authors were compared with our findings (Table ), and Ti, Mn, and Fe were found in all samples in our research and work of Melquiades et al . This is because titanium is used in eyeshadow formulations as opacifier and ultraviolet radiation absorber in the form of titanium dioxide (Color Index: CI 77891) and, when added titanium element, add dye function; being the basic compound for any cosmetic powder formulation.…”
Section: Resultsmentioning
confidence: 99%
“…As was previously mentioned, bismuth acts as a lubricant in lipstick, and some cosmetic formulations still use barium in the form of barium sulfate. [31] Eyeliner: To bring more attention to the shape of the eyes, it is applied to the tops of the eyelids. Eyeliners are available in liquid and pencil form.…”
Section: Toxicology Of Cosmetics and Its Usesmentioning
confidence: 99%
“…Variations in potassium, titanium, and iron concentration are correlated with sample shadow tones, decreasing with higher concentrations being related to the samples' dark coloring. [31] Vermillion: Hindu women apply vermilion/sindoor, a brilliant red/scarlet pigment, to their foreheads where their hair is parted. [29] Bright orange, a duller bluish red, red, and maroon version of vermilion are also available.…”
Section: Toxicology Of Cosmetics and Its Usesmentioning
confidence: 99%
“…Qualitative and quantitative determination of major, minor and trace elements can be done with the help of Energy Dispersive X‐Ray Fluorescence (EDXRF) technique. For example, the elemental constituents of metals, alloys, glasses, cements, minerals rocks, ores, polymers and biomaterials have been determined using EDXRF . The uniqueness of EDXRF is that it is non destructive technique; hence, it is widely applied to the study of arts, pottery, glasses, ceramics, coins paiting and icons.…”
Section: Introductionmentioning
confidence: 99%